IMAGERY FOUND IN ELIZABETH ALEXANDER POETRY’S - gusti ngurah, kaler (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2023)
This lesson is entitled "Analysis of Imagery and Meaning found in Elizabeth Alexandre's Poerty." This lesson focuses on each type of imagery contained in Elizabeth Alexandre's poetry. This study identifies imagery and meaning in this poem and the data is taken from the stanzas analyzed in Elizabeth Alexandre's poetry. The data of this study were analyzed using a qualitative descriptive method. The first step of the analysis is observing the collected data, then classifying the data based on the type of imagery that occurs in Elizabeth Alexander's poetry lyrics using the theory of Arp & Perrine (1991).